2018
DOI: 10.1387/ijdb.170327ss
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of etoposide-induced 2.4 kb transcript (ei24) reduced cell proliferation and aggregate-size in Dictyostelium discoideum

Abstract: The etoposide-induced 2.4 kb transcript (ei24) gene is induced both by p53 and etoposide, an anti-cancer tumour drug. There is no p53 gene present in Dictyostelium discoideum. Thus, the functions of ei24 in the absence of p53 were analysed. Both overexpressor (ei24) and knockout (ei24) mutants were made to study its role during growth, development and differentiation. Additionally, cell cycle and its response to DNA-damage were also analysed. We identified, characterized and elucidated the functions of the ei2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…They suggested that EI24 acts as a tumor suppressor in skin cancer. Additionally, it has been reported that EI24 is involved in the survival and growth of non-tumor cells such as pancreatic β-cells and Dictyostelium discoideum (21, 22). EI24 has been reported as a tumor suppressor even in pancreatic cancer cells, which is in conflict with our observations (23).…”
Section: Discussionmentioning
confidence: 99%
“…They suggested that EI24 acts as a tumor suppressor in skin cancer. Additionally, it has been reported that EI24 is involved in the survival and growth of non-tumor cells such as pancreatic β-cells and Dictyostelium discoideum (21, 22). EI24 has been reported as a tumor suppressor even in pancreatic cancer cells, which is in conflict with our observations (23).…”
Section: Discussionmentioning
confidence: 99%
“…The absorbance was read at 405 nm. All measurements were normalized to protein concentrations determined by Bradford assay 11 …”
Section: Methodsmentioning
confidence: 99%
“…All measurements were normalized to protein concentrations determined by Bradford assay. 11 2.9 | Reactive oxygen species (ROS) levels 6×10 6 cells/ml were incubated with 30 μM Dihydroethidium (D7008; Sigma-Aldrich) for 30 min in the dark, washed twice in chilled KK2 buffer and immediately processed for flow-cytometer (BD-FACSAria Fusion). 12…”
Section: Camp Levelsmentioning
confidence: 99%
“…For the first time, they showed that apart from being an energy sensor, AMPK also has a role in aggregate-size determination and cell patterning (Maurya et al, 2018). Saran's interest in the etoposide-induced 2.4 kb transcript (ei24) gene that is induced both by p53 and etoposide, an anti-cancer tumour drug allowed to understand its role in D. discoideum which does not possess a p53 protein (Gupta and Saran, 2018). Their work shows that EI24 (an autophagy associated transmembrane protein) is a key protein involved in autophagy (Gupta and Saran, 2019).…”
Section: Developmental Cell Deathmentioning
confidence: 99%